Coaxial gradient porous nano core-shell structure cathode material and preparation method thereof
The coaxial gradient porous nano core-shell structure cathode material prepared by coaxial air spray spinning and chemical modification processes solves the problems of low zinc storage capacity and insufficient energy density of existing materials, and achieves efficient energy storage and release.
Patent Information
- Application Number
- CN202411578853.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The cathode materials of existing zinc ion batteries have low zinc storage capacity, and the single pore structure of traditional carbon-based materials cannot take into account high energy density and high power output.
The cathode material with excellent electrochemical properties is prepared by coaxial gradient porous nano core-shell structure through coaxial air spray spinning and chemical modification processes. The material consists of conductive carbon nanomaterials and polymers, and forms a gradient pore structure through multi-step chemical modification and heat treatment.
It significantly improves the energy storage performance and cycle stability of zinc ion batteries, and achieves a balance between high energy density and high power output.
Smart Images

Figure CN119686025A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a coaxial gradient porous nano core-shell structure cathode material and a preparation method thereof. Background Art
[0002] With the continuous increase in energy demand and the increasingly serious environmental problems, it is particularly important to develop efficient and environmentally friendly energy storage technologies. Zinc-ion batteries have gradually become an energy storage technology with broad application prospects due to their high safety, low cost, and environmental friendliness. Zinc, as an ideal anode material for aqueous zinc-ion batteries, has the characteristics of rapid deposition / stripping redox reactions, and can achieve high power density and long service life. In the research on cathode materials for zinc-ion batteries, manganese-based compounds (such as MnO2, Mn3O4), vanadium-based compounds (such as V2O5, Na3V2(PO4)3) and Prussian blue materials have attracted a lot of research attention due to their high theoretical capacity and good electrochemical properties.
[0003] Carbon-based materials can also be used as cathode materials for zinc-ion batteries. The zinc storage capacity of traditional carbon-based materials (such as graphite and activated carbon with high specific surface area and good conductivity) is often low, which limits their application in zinc-ion batteries. However, carbon-based materials have unique advantages, such as light weight, low cost, environmental friendliness and excellent conductivity. By engineering carbon materials, especially introducing appropriate pore structures and functionalized surfaces, their zinc storage capacity and electrochemical performance can be significantly improved. For example, carbonaceous materials with high specific surface area and appropriate pore size are conducive to achieving high-density zinc storage, but a single type of pore structure alone often cannot take into account both high energy density and high power output. Therefore, carbon materials with gradient pore structures have emerged. This structure can not only improve the zinc storage capacity, but also optimize the electron transport and ion diffusion paths, thereby achieving efficient energy storage and release. Therefore, the development of a zinc-ion battery cathode material with a gradient porous nanocore-shell structure is of great significance for improving the performance of zinc-ion batteries.
[0004] Patent CN116722121A chemically modifies the surface of carbon-based materials and coats vanadium-based oxide positive electrode materials with redox-active carbon-based materials, emphasizing the rate performance of vanadium-based positive electrode materials and the structural stability and specific surface area of carbon-based materials, but does not involve gradient porous structures and engineering design of carbon-based materials to improve zinc storage capacity. Patent CN110828802A uses electrospinning to prepare a composite positive electrode material of graphene-coated manganese sulfide and nitrogen-doped carbon nanofibers, which improves the specific capacity of the battery positive electrode, has excellent cycle stability, and can achieve high-rate charge and discharge, but the production efficiency of electrospinning is low, which is not conducive to the mass production and large-scale application of cathodes. Patent CN114335471A derives manganese oxide from Mn-MOF, and then heat treats it in an argon atmosphere to obtain MnO / C. The material inherits the advantages of Mn-MOF's porosity and large specific surface area, providing great advantages for ion diffusion and electron transfer, but it does not improve the performance by improving the structure of carbon-based materials, especially the effect of gradient pores on zinc ion storage and battery performance. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a coaxial gradient porous nano core-shell structure cathode material and a preparation method thereof, and prepare a zinc ion battery cathode material with excellent electrochemical properties through coaxial air-jet spinning and chemical modification process, which is widely used in the field of energy storage and conversion.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a coaxial gradient porous nano core-shell structure cathode material, comprising the following steps:
[0008] (1) dissolving a conductive carbon nanomaterial and a high molecular polymer in a solvent to obtain a precursor solution A; dissolving a styrene-acrylonitrile copolymer (SAN) and a high molecular polymer in a solvent to obtain a precursor solution B; injecting the precursor solution A into the outer channel of a coaxial air nozzle, and injecting the precursor solution B into the inner channel of the coaxial air nozzle, or injecting the precursor solution A into the inner channel of the coaxial air nozzle, and injecting the precursor solution B into the outer channel of the coaxial air nozzle, and performing coaxial air-jet spinning to obtain an air-jet spinning membrane with a nano core-shell structure; the conductive carbon nanomaterial is selected from one or more of carbon quantum dots (CDs), graphene quantum dots (GQDs), carbon nanotubes (CNTs), fullerene (C60) and graphene oxide (GO); the high molecular polymer is selected from one or more of polyacrylonitrile (PAN), polyamic acid (PAA), polybenzimidazole (PBI), polypyrrole (PPy) and polyetherimide (PEI);
[0009] (2) immersing the air-jet spinning membrane with a nano core-shell structure obtained in step (1) into a 3-aminophenol solution, then adding methyltriethoxysilane (VTMS) and ammonia water, and then injecting a formaldehyde solution to obtain a surface-modified air-jet spinning membrane with a nano core-shell structure;
[0010] (3) subjecting the surface-modified air-jet spinning membrane with a nano core-shell structure obtained in step (2) to a pyrolysis carbonization treatment in an inert atmosphere to obtain a nano hybrid carbon fiber membrane material with a porous structure;
[0011] (4) using an acid solution to treat the nano hybrid carbon fiber membrane material with a porous structure obtained in step (3), mixing the treated material with a strong alkaline solution, and performing a carbonization treatment in an inert atmosphere to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0012] The preparation method provided by the present invention prepares a cathode material with a high specific surface area and excellent electrochemical properties by introducing conductive carbon nanomaterials and optimized air-jet spinning technology and constructing a gradient pore structure through chemical modification, thereby significantly improving the energy storage performance and cycle stability of zinc ion batteries.
[0013] Furthermore, in step (1), the molecular weight of the styrene-acrylonitrile copolymer is 80,000-150,000 g / mol.
[0014] Furthermore, in step (1), the molecular weight of the high molecular weight polymer is 100,000-150,000 g / mol.
[0015] Furthermore, in step (1), the mass ratio of the conductive carbon nanomaterial to the high molecular polymer is (0.5-1):(10-15); the mass ratio of the styrene-acrylonitrile copolymer to the high molecular polymer is (5-10):(10-15).
[0016] Furthermore, in step (1), the concentration of the conductive carbon nanomaterial in the precursor solution A is 10-15 wt %; and the concentration of the styrene-acrylonitrile copolymer in the precursor solution B is 5-20 wt %.
[0017] In a specific embodiment, in step (1), the conductive carbon nanomaterial is dispersed in a solvent and ultrasonically treated to ensure uniform dispersion; PAN is dissolved in the above solution and stirred until completely dissolved to obtain a precursor solution A of a PAN-based component doped with CDs having a concentration of 10-15wt%; SAN is dissolved in a solvent and stirred until completely dissolved; PAN is added to the above solution and stirred until completely dissolved to obtain a precursor solution B of a PAN-based component doped with SAN having a concentration of 5-20wt%.
[0018] Furthermore, in step (1), the solvent is selected from one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).
[0019] Furthermore, in step (1), the conductive carbon nanomaterial is preferably carbon quantum dots (CDs).
[0020] The doping of CDs is more beneficial to improving the conductivity and the pore distribution of the core layer.
[0021] Furthermore, in step (1), the high molecular polymer is preferably polyacrylonitrile (PAN).
[0022] The coaxial gradient porous nano core-shell structure cathode material prepared by the present invention is composed of a nanofiber porous core and a nano outer shell with a gradient pore structure, wherein the nanofiber porous core is a PAN-based component doped with SAN, and the nano outer shell with a gradient pore structure is a PAN-based component doped with CDs, and the nano outer shell has excellent electrical conductivity; or the coaxial gradient porous porous nano core-shell structure cathode material is composed of a nanofiber porous core and a nanofiber porous outer shell, wherein the core with a gradient pore structure is a PAN-based component doped with CDs, and the nanofiber porous outer shell is a PAN-based component doped with SAN, wherein CDs as the core provides an efficient electron conduction path, and SAN as the outer shell ensures the mechanical strength and pore structure stability of the material, and this combination has good comprehensive performance, especially in the balance between electrical conductivity and mechanical strength.
[0023] Furthermore, the diameter of the nanofiber porous core is 100-500 nanometers, and the thickness of the nano outer shell with gradient pore structure is 150-800 nanometers.
[0024] In the present invention, the precursor solution will help to form a fiber membrane material with uniform nanostructure and excellent performance in the subsequent coaxial air-jet spinning process. In addition, air-jet spinning is more suitable for large-scale production, and the material processing of air-jet spinning is more diversified.
[0025] Furthermore, in step (1), the process parameters of the coaxial air-jet spinning are: the jet rate of the inner channel is 0.5-2.0 mL / h; the jet rate of the outer channel is 1.0-5.0 mL / h.
[0026] Furthermore, in step (1), after coaxial air-jet spinning is carried out, an air-jet spinning membrane having a nano core-shell structure is obtained on the receiver.
[0027] Furthermore, in step (2), the concentration of 3-aminophenol in the 3-aminophenol solution is 0.1-1 mol / L.
[0028] Furthermore, in step (2), the volume ratio of the 3-aminophenol solution, methyltriethoxysilane, ammonia water and formaldehyde solution is 5:(0.5-1.5):(0.5-1.5):(0.5-1.5).
[0029] Furthermore, in step (2), the volume ratio of methyltriethoxysilane to aqueous ammonia is preferably 1:1.
[0030] Furthermore, in step (2), the air-jet spinning membrane with a nano core-shell structure obtained in step (1) is immersed in a 3-aminophenol solution and stirred for 5-10 minutes, then methyltriethoxysilane and ammonia water are added, stirred for 5-6 hours, and then a formaldehyde solution is injected, stirred at 20-25°C for 5-6 hours, and dried to obtain a surface-modified air-jet spinning membrane with a nano core-shell structure.
[0031] Step (2) performs a multifunctional surface modification, which combines the surface functionalization of silicone and aminophenol groups, and forms an organic-inorganic hybrid core-shell structure through aminophenol-silicone synergistic surface functionalization treatment.
[0032] Furthermore, in step (2), the concentration of the formaldehyde solution is 5-15wt%.
[0033] Furthermore, in step (3), the temperature of the pyrolysis carbonization treatment is 750-800°C.
[0034] Furthermore, in step (3), the inert atmosphere can be argon, nitrogen, helium, neon, etc.
[0035] Furthermore, in step (4), the acid solution is a hydrofluoric acid (HF) solution with a concentration of 10%-15%.
[0036] Furthermore, in step (4), the acid solution treatment time is 2-4 hours.
[0037] Furthermore, in step (4), the mass ratio of the treated material to the strong alkaline solution is 1:(3-7).
[0038] During the carbonization process, strong alkali can be used as an activator to form rich micropores and mesoporous structures in the material through a combination of chemical reactions and physical etching. During the high-temperature carbonization process, strong alkali will undergo redox reactions with carbon materials to generate gases such as carbon monoxide (CO) and carbon dioxide (CO2). The generation of these gases causes the expansion of the carbon structure and the formation of pores. For example, KOH can react with carbon materials to generate K2CO3, which further decomposes to generate CO2 and produce additional pores. These reactions take place on the pore walls, resulting in surface erosion and increased pore size. In addition, the CO and CO2 generated during carbonization etch the microstructure inside the material, further forming a porous structure. This gas etching can break the inherent structure of the carbon material, further refine and expand the pore size, thereby optimizing the porosity of the material.
[0039] When the carbonization temperature reaches a certain level (e.g. above 750°C), KOH will decompose to produce metallic potassium. The volume of metallic potassium is large and can be embedded in the interlayer of carbon materials, causing the expansion of the layered structure and enhancing the generation of pores. This embedding and expansion effect can effectively expand the pore size distribution range and help form mesopores and micropores.
[0040] The presence of strong alkali is not just a simple etching, it can also further activate the carbon-based material during the carbonization process and increase its specific surface area. This activation increases the reaction sites of the material, which is beneficial to the electrochemical reaction of zinc ions and the construction of ion migration channels.
[0041] Strong alkali has both chemical reaction and physical etching effects during high-temperature carbonization. It significantly increases the porosity of the material through redox reactions, gas etching, and metallic potassium embedding, and regulates the pore size and pore distribution, ultimately forming an ideal microporous-mesoporous structure to meet the needs of zinc ion transport.
[0042] Furthermore, in step (4), the strong alkaline solution may be a potassium hydroxide (KOH) solution, a sodium hydroxide (NaOH) solution, or the like.
[0043] Furthermore, in step (4), the concentration of the strong alkaline solution is 5-10 mol / L.
[0044] Furthermore, in step (4), the specific operation of the carbonization treatment is: heating to 700-800°C at a heating rate of 1-3°C / min and maintaining for 0.5-2h.
[0045] Furthermore, in step (4), after the carbonization treatment is completed, the step of washing with hydrochloric acid solution and water until neutrality is achieved and then drying is performed.
[0046] Furthermore, the concentration of the hydrochloric acid solution is 1-3 mol / L.
[0047] Furthermore, the electrical conductivity of the water is less than 1 μS / cm.
[0048] Furthermore, the water is preferably deionized water.
[0049] Furthermore, the drying temperature is 60-80°C and the drying time is 8-12h.
[0050] The second aspect of the present invention protects the coaxial gradient porous nano core-shell structure cathode material prepared by the method described in the first aspect.
[0051] The cathode material prepared by the present invention has a dual-path fiber structure of axial electron transport and radial ion diffusion, and combined with gradient mesoscopic micropores, it will further optimize the high energy storage and power output of carbonaceous materials. It has good electrochemical properties and structural stability and is suitable for high-performance zinc-ion batteries.
[0052] The coaxial gradient porous nano core-shell structure cathode material provided by the invention can be used in zinc ion batteries.
[0053] Beneficial effects of the present invention:
[0054] 1. The conductive carbon nanomaterial used in the present invention has excellent conductivity and high specific surface area. By doping in high molecular polymers, the conductive properties and electrochemical activity of cathode materials can be significantly improved. At the same time, the presence of conductive carbon nanomaterials provides more active sites, which is conducive to the rapid adsorption and desorption of zinc ions, thereby improving the storage capacity of zinc ions and the energy density of the battery. The addition of SAN enhances the mechanical strength and stability of the shell material. The SAN-doped shell not only provides structural support, but also increases the chemical stability of the material, extending the service life of the battery.
[0055] 2. Compared with the traditional electrospinning method, the coaxial air-jet spinning method of the present invention has higher efficiency and better controllability. By precisely controlling the flow rate and air-jet pressure of the inner and outer layer solutions, the uniform formation of the core-shell structure can be achieved; the optimization of the spinning distance further ensures the formation quality and structural integrity of the fiber. The present invention adopts multi-step chemical modification and heat treatment. Through multi-step chemical modification in 3-aminophenol, VTMS, ammonia water and formaldehyde, the shell structure is further strengthened. The subsequent pyrolysis carbonization and acid solution treatment steps make the material have a gradient porous structure, which significantly improves the electrochemical performance.
[0056] 3. The present invention can accurately control the pore size and distribution in the carbon material by adjusting the concentration of the strong alkaline solution to form a gradient pore structure. This structure not only enhances the specific surface area of the material, but also optimizes the pore structure, making it more suitable for use as a cathode material for high-performance zinc ion batteries. The gradient pore structure facilitates the rapid transmission and uniform distribution of zinc ions, thereby significantly improving the electrochemical performance of the battery.
[0057] 4. The coaxial gradient porous nano core-shell structure cathode material prepared by the present invention has a core-shell structure that not only provides excellent mechanical properties and structural stability, but also greatly improves the storage capacity of zinc ions. The gradient porous structure facilitates the rapid transmission and uniform distribution of zinc ions, reduces the ion transmission resistance inside the battery, and further improves the power density and cycle stability of the battery.
[0058] 5. The present invention significantly improves the electrochemical performance and service life of the cathode material of the zinc ion battery through the reasonable selection of doping materials, optimized preparation process and innovative structural design, and provides new ideas and methods for the development of high-performance zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The present invention provides a process flow chart of the preparation method of the coaxial gradient porous nano core-shell structure cathode material.
[0060] Figure 2 This is a schematic structural diagram of the coaxial gradient porous nano core-shell structure cathode material prepared in Example 1. DETAILED DESCRIPTION
[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0062] The present invention provides a method for preparing a coaxial gradient porous nano core-shell structure cathode material, such as Figure 1 As shown, the following steps are included:
[0063] (1) dissolving a conductive carbon nanomaterial and a high molecular polymer in a solvent to obtain a precursor solution A; dissolving a styrene-acrylonitrile copolymer (SAN) and a high molecular polymer in a solvent to obtain a precursor solution B; injecting the precursor solution A and the precursor solution B into the outer channel and the inner channel of a coaxial air nozzle, respectively, or injecting the precursor solution A and the precursor solution B into the inner channel and the outer channel of a coaxial air nozzle, respectively, to perform coaxial air-jet spinning to obtain an air-jet spinning membrane having a nano core-shell structure;
[0064] (2) immersing the air-jet spinning membrane having a nano core-shell structure obtained in step (1) into a 3-aminophenol solution, then adding methyltriethoxysilane and ammonia water, and then injecting a formaldehyde solution to obtain a surface-modified air-jet spinning membrane having a nano core-shell structure;
[0065] (3) subjecting the surface-modified air-jet spinning membrane with a nano core-shell structure obtained in step (2) to a pyrolysis carbonization treatment in an inert atmosphere to obtain a nano hybrid carbon fiber membrane material with a porous structure;
[0066] (4) using an acid solution to treat the nano hybrid carbon fiber membrane material with a porous structure obtained in step (3), mixing the treated material with a strong alkaline solution, and performing a carbonization treatment in an inert atmosphere to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0067] In a specific embodiment, the preparation method of the precursor solution A is as follows: the conductive carbon nanomaterial is dispersed in a solvent, and an ultrasonic treatment method is used to ensure the uniformity of the dispersion, the treatment time is 30-40 minutes, and the ultrasonic frequency is 40-50kHz. Subsequently, PAN is slowly added to the above-mentioned uniformly dispersed conductive carbon nanomaterial solution, and continuous stirring is performed to promote the complete dissolution of PAN. The stirring conditions are 500-600rpm at room temperature, and the stirring time is 4-5 hours, and finally a precursor solution A of a PAN-based component doped with a conductive carbon nanomaterial is obtained.
[0068] In a specific embodiment, the preparation method of the precursor solution B is as follows: SAN is dissolved in a solvent, and magnetic stirring is performed at room temperature until SAN is completely dissolved, the stirring rate is 500-600 rpm, and the stirring time is 2-3 hours. Subsequently, PAN is slowly added to the above-mentioned completely dissolved SAN solution, and stirring is continued to ensure that PAN is fully dissolved, the stirring conditions are 500-600 rpm at room temperature, and the stirring time is 4-5 hours, and finally a precursor solution B of a SAN-doped PAN-based component is obtained.
[0069] In a specific embodiment, the conductive carbon nanomaterial is selected from one or more of carbon quantum dots (CDs), graphene quantum dots (GQDs), carbon nanotubes (CNTs), fullerene (C60) and graphene oxide (GO); the high molecular polymer is selected from one or more of polyacrylonitrile (PAN), polyamic acid (PAA), polybenzimidazole (PBI), polypyrrole (PPy) and polyetherimide (PEI).
[0070] In a specific embodiment, in step (1), the operation of coaxial air-jet spinning is as follows: precursor solution A and precursor solution B are respectively injected into the inner and outer channels of the coaxial air-jet nozzle to perform coaxial air-jet spinning, and the diameter of the fiber core and the thickness of the outer shell layer in the nanofiber are regulated by changing the spinning flow rate and the air-jet pressure to obtain air-jet spinning membranes with nano core-shell structures of different structures on the receiver, and then the fibers are dried in a drying oven at 60-80°C for 10-20 hours.
[0071] In a specific embodiment, in step (1), the process parameters of the coaxial air-jet spinning are: the injection rate of the inner channel is 0.5-2.0 mL / h, the injection rate of the outer channel is 1.0-5.0 mL / h, the air jet pressure is 0.2-0.3 MPa, and the spinning distance is 10-20 cm.
[0072] In a specific embodiment, in step (2), the air-jet spun membrane with a nano core-shell structure obtained in step (1) is cut into samples of suitable size, immersed in a 3-aminophenol solution, stirred for 5-10 minutes, and then methyltriethoxysilane and ammonia water are added, stirred for 5-6 hours, and then a formaldehyde solution is injected, stirred at 20-25°C for 5-6 hours, and then the sample is dried overnight to obtain a surface-modified air-jet spun membrane with a nano core-shell structure.
[0073] In a specific embodiment, in step (3), the surface-modified air-blown spinning membrane with a nano core-shell structure obtained in step (2) is subjected to pyrolysis carbonization treatment in an inert atmosphere, heated to 750-800°C at a heating rate of 2-3°C / min, and maintained for 2-3 hours, and then naturally cooled to room temperature to obtain a nano hybrid carbon fiber membrane material with a porous structure.
[0074] In a specific embodiment, in step (4), the nano hybrid carbon fiber membrane material with a porous structure obtained in step (3) is treated with an acid solution at room temperature for 30-40 minutes, and then washed with deionized water until neutral; the treated material is mixed with a strong alkaline solution, carbonized in an inert atmosphere, heated to 700-800°C at a heating rate of 1-3°C / min, maintained for 0.5-2h, then washed with hydrochloric acid solution and deionized water until neutral, and dried overnight in a constant temperature forced air drying oven at 70-80°C to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0075] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0076] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0077] In the following embodiments, carbon quantum dots were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with a product number of 102632; polyacrylonitrile was purchased from Shanghai Guchen Biotechnology Co., Ltd. with a product number of GC25168-500gA; styrene-acrylonitrile was purchased from Guangzhou Zhongxin Plastic Co., Ltd.; dimethyl sulfoxide was purchased from Shandong Jinhe Chemical Co., Ltd. with a density of 1.100 g / mL; 3-aminophenol was purchased from Nanjing Chemical Reagent Co., Ltd. with a product number of C0480559335; methyltriethoxysilane was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a purity of AR grade; formaldehyde was purchased from Nanjing Chemical Reagent Co., Ltd.; hydrofluoric acid was purchased from Shanghai Yien Chemical Technology Co., Ltd. with a purity of AR grade; potassium hydroxide was purchased from Xilong Science Co., Ltd.; hydrochloric acid was purchased from Shenzhen Bolinda Technology Co., Ltd. with a concentration of 2 mol / L; and argon was purchased from Shanghai Jinzhu Chemical Co., Ltd.
[0078] Example 1
[0079] A method for preparing a coaxial gradient porous nano core-shell structure cathode material comprises the following steps:
[0080] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air-jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0081] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0082] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0083] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 6 mol / L KOH solution at a mass ratio of 1:3, carbonizing it in an argon atmosphere, heating it to 750°C at a heating rate of 2°C / min, maintaining it for 1 hour, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 70°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0084] Figure 2This is a schematic diagram of the structure of the coaxial gradient porous nano core-shell structure cathode material prepared in Example 1. The inner layer represents a nanofiber porous core composed of SAN-doped PAN-based materials, and its function is to provide high conductivity and structural support. The outer layer is a gradient porous structure, which is a nanoshell composed of CDs-doped PAN-based materials. This gradient pore structure is achieved through a specific treatment concentration with the KOH solution, which can optimize the transmission path of zinc ions and improve the electrochemical properties of the material. The gradient pores exist on the surface of the outer carbon quantum dots, which are composed of micropores and mesopores. The micropores exist on the surface of the carbon quantum dots, and the mesopores are distributed on the micropores. The present invention provides an effective method for the design of mesoporous and microporous carbon materials to achieve high energy density energy storage.
[0085] Example 2
[0086] A method for preparing a coaxial gradient porous nano core-shell structure cathode material comprises the following steps:
[0087] (1) Disperse 15g of CDs in 100mL of DMSO solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 20g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 20g of SAN in 100mL of DMSO solution and perform magnetic stirring at 500rpm for 2h at room temperature until completely dissolved. Subsequently, slowly add 20g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.7 mL / h, the injection rate of the outer channel was 1.2 mL / h, the air-jet pressure was 0.25 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0088] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 15 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 8 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 8 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0089] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0090] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 6 mol / L KOH solution at a mass ratio of 1:5, carbonizing it in an argon atmosphere, heating it to 700°C at a heating rate of 3°C / min, maintaining it for 2 hours, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 80°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0091] Example 3
[0092] A method for preparing a coaxial gradient porous nano core-shell structure cathode material comprises the following steps:
[0093] (1) Disperse 15g of CDs in 100mL of DMSO solution and perform ultrasonic treatment for 40min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 25g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 5h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 25g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 3h until completely dissolved. Subsequently, slowly add 25g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 5h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.6 mL / h, the injection rate of the outer channel was 1.1 mL / h, the air-jet pressure was 0.22 MPa, the spinning distance was 14 cm, and an air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0094] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 12 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 7 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 7 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0095] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0096] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 6 mol / L KOH solution at a mass ratio of 1:7, carbonizing it in an argon atmosphere, heating it to 720°C at a heating rate of 2.5°C / min, maintaining it for 1.5 hours, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 75°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0097] Example 4
[0098] A method for preparing a coaxial gradient porous nano core-shell structure cathode material is basically the same as that of Example 1, except that in step (4), the treated material is mixed with a 6 mol / L KOH solution at a mass ratio of 1:1.
[0099] Example 5
[0100] A method for preparing a coaxial gradient porous nano core-shell structure cathode material is basically the same as that of Example 1, except that in step (4), the treated material is mixed with a 6 mol / L KOH solution at a mass ratio of 1:5.
[0101] Example 6
[0102] A method for preparing a coaxial gradient porous nano core-shell structure cathode material is basically the same as that of Example 1, except that in step (4), the treated material is mixed with a 6 mol / L KOH solution at a mass ratio of 1:7.
[0103] Example 7
[0104] A method for preparing a coaxial gradient porous nano core-shell structure cathode material is basically the same as that of Example 1, except that in step (4), the treated material is mixed with a 6 mol / L KOH solution at a mass ratio of 1:10.
[0105] Example 8
[0106] A method for preparing a coaxial gradient porous nano core-shell structure cathode material comprises the following steps:
[0107] (1) Disperse 15g of carbon nanotubes (CNTs) in 100mL of DMSO solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 20g of PAN to the uniformly dispersed CNTs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CNTs. Dissolve 20g of SAN in 100mL of DMSO solution and perform magnetic stirring at 500rpm for 2h at room temperature until completely dissolved. Subsequently, slowly add 20g of PAN to the completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a SAN-based component doped with PAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.7 mL / h, the injection rate of the outer channel was 1.2 mL / h, the air-jet pressure was 0.25 MPa, the spinning distance was 15 cm, and an air-jet spinning membrane with a CNTs@SAN nano core-shell structure was obtained on the receiver.
[0108] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 15 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 8 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 8 h, and then the sample was dried overnight to obtain an air-blown membrane with a CNTs@organic silicon@APF nano core-shell structure.
[0109] (3) The air-blown spinning membrane with a CNTs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0110] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 6 mol / L KOH solution at a mass ratio of 1:5, carbonizing it in an argon atmosphere, heating it to 700°C at a heating rate of 3°C / min, maintaining it for 2 hours, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 80°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0111] Example 9
[0112] A method for preparing a coaxial gradient porous nano core-shell structure cathode material comprises the following steps:
[0113] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the inner channel of the coaxial air nozzle, and the precursor solution B was injected into the outer channel of the coaxial air nozzle for coaxial air jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air jet spinning membrane with a SAN@CDs nano core-shell structure was obtained on the receiver.
[0114] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a SAN@CDs@organic silicon@APF nano core-shell structure.
[0115] (3) The air-blown spinning membrane with the SAN@CDs@organic silicon@APF nano core-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0116] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 6 mol / L KOH solution at a mass ratio of 1:3, carbonizing it in an argon atmosphere, heating it to 750°C at a heating rate of 2°C / min, maintaining it for 1 hour, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 70°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0117] Comparative Example 1
[0118] A method for preparing a nano-hybrid carbon fiber membrane material with a porous structure comprises the following steps:
[0119] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air-jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0120] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0121] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0122] Comparative Example 2
[0123] A method for preparing a porous nano core-shell structure cathode material comprises the following steps:
[0124] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air-jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0125] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0126] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0127] (4) The nano-hybrid carbon fiber membrane material with a porous structure is immersed in a 10% HF solution, treated at room temperature for 30 minutes, then washed with deionized water until neutral, carbonized in an argon atmosphere, heated to 750°C at a heating rate of 2°C / min, maintained for 1 hour, then washed with 1 mol / L hydrochloric acid solution and deionized water until neutral, and dried in a constant temperature forced air drying oven at 70°C overnight to obtain the porous nano-core-shell structure cathode material.
[0128] Comparative Example 3
[0129] A method for preparing a porous nano core-shell structure cathode material comprises the following steps:
[0130] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air-jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0131] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0132] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0133] (4) The nano-hybrid carbon fiber membrane material with a porous structure was mixed with a 6 mol / L KOH solution at a mass ratio of 1:5, and carbonized in an argon atmosphere. The temperature was increased to 750°C at a heating rate of 2°C / min and maintained for 1 hour. The mixture was then washed with a 1 mol / L hydrochloric acid solution and deionized water until neutral, and dried in a constant temperature forced air drying oven at 70°C overnight to obtain the coaxial gradient porous nano-core-shell structure cathode material.
[0134] Comparative Example 4
[0135] A method for preparing a porous nano core-shell structure cathode material comprises the following steps:
[0136] (1) Disperse 15g of CDs in 100mL of dimethyl sulfoxide (DMSO) solution and perform ultrasonic treatment for 30min to ensure uniform dispersion at an ultrasonic frequency of 40kHz. Subsequently, slowly add 15g of PAN to the above uniformly dispersed CDs solution and continue stirring until completely dissolved at 500rpm at room temperature for 4h to obtain a precursor solution A of a PAN-based component doped with CDs. Dissolve 10g of SAN in 100mL of DMSO solution and perform magnetic stirring at a stirring rate of 500rpm at room temperature for 2h until completely dissolved. Subsequently, slowly add 15g of PAN to the above completely dissolved SAN solution and stir at 500rpm at room temperature for 4h to obtain a precursor solution B of a PAN-based component doped with SAN. The precursor solution A was injected into the outer channel of the coaxial air nozzle, and the precursor solution B was injected into the inner channel of the coaxial air nozzle for coaxial air-jet spinning. The injection rate of the inner channel was 0.5 mL / h, the injection rate of the outer channel was 1.0 mL / h, the air-jet pressure was 0.2 MPa, and the spinning distance was 15 cm. An air-jet spinning membrane with a CDs@SAN nano core-shell structure was obtained on the receiver.
[0137] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 10 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 6 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 °C for 6 h, and then the sample was dried overnight to obtain an air-blown membrane with a CDs@organic silicon@APF nano core-shell structure.
[0138] (3) The air-blown spinning membrane with a CDs@organic silicon@APF nanocore-shell structure was subjected to pyrolysis carbonization treatment in an argon atmosphere, heated to 800°C at a heating rate of 2°C / min, maintained for 2 h, and then naturally cooled to room temperature to obtain a nano-hybrid carbon fiber membrane material with a porous structure.
[0139] (4) Immersing the nano-hybrid carbon fiber membrane material with a porous structure in a 10% HF solution, treating it at room temperature for 30 minutes, and then washing it with deionized water until it is neutral; mixing the treated material with a 1-1.5 mol / L Na2CO3 solution at a mass ratio of 1:7, carbonizing it in an argon atmosphere, heating it to 750°C at a heating rate of 2°C / min, maintaining it for 1 hour, then washing it with a 1 mol / L hydrochloric acid solution and deionized water until it is neutral, and drying it in a constant temperature forced air drying oven at 70°C overnight to obtain the coaxial gradient porous nano core-shell structure cathode material.
[0140] Comparative Example 5
[0141] A method for preparing an electrospinning membrane cathode material having a V2O5 / C structure comprises the following steps:
[0142] (1) 2 g of vanadium-based oxide (V2O5) was dispersed in 100 mL of deionized water and ultrasonically treated for 30 min to ensure uniform dispersion at an ultrasonic frequency of 40 kHz. Subsequently, 2 g of polyvinyl alcohol (PVA) was slowly added to the uniformly dispersed V2O5 solution and stirred continuously until completely dissolved at 500 rpm at room temperature for 4 h to obtain a precursor solution of a V2O5-doped PVA-based component. The precursor solution was injected into an electrospinning device with a flow rate set at 0.5 mL / h, a voltage of 20 kV, and a spinning distance of 10 cm to obtain an electrospinning membrane having a V2O5 / PVA structure on a receiver.
[0143] (2) The air-blown membrane was cut into 2 cm × 2 cm samples, immersed in 50 mL of 0.1 mol / L 3-aminophenol solution, stirred for 15 min, then 10 mL of methyltriethoxysilane and 10 mL of ammonia water were added, stirred for 8 h, and then 10 mL of 10 wt% formaldehyde solution was injected, stirred at 25 ° C for 8 h, and then the sample was dried overnight to obtain an electrospun membrane cathode material with a V2O5 / C structure.
[0144] The cathode materials prepared in Examples 1-9 and Comparative Examples 1-5 were subjected to performance tests in terms of tensile strength, specific surface area, pore size distribution, specific capacity, energy density, cycle stability, charge transfer resistance, etc. The tensile strength test was performed in accordance with GB / T 10654-2001; the specific surface area test was performed in accordance with GB / T 19587-2017; the pore size distribution test was performed in accordance with GB / T 21650.3-2011; the specific capacity test was performed in accordance with SJ / T 11793-2022; the energy density test was performed in accordance with SJ / T 11793-2022; the cycle stability test was performed in accordance with SJ / T 11793-2022; the charge transfer resistance was obtained by electrochemical impedance spectroscopy test, and the test results are shown in Table 1:
[0145] Table 1
[0146]
[0147]
[0148] According to the data analysis in Table 1, compared with other embodiments and comparative examples, the coaxial gradient porous nano core-shell structure cathode material prepared in Example 5 shows significant advantages in electrochemical performance. Specifically, the specific capacity of the cathode material reaches 300mAh / g, and the energy density is as high as 190Wh / kg, showing excellent energy storage capacity. In addition, after 500 charge and discharge cycles, its capacity retention rate is still as high as 98%, showing excellent cycle stability. At the same time, the charge transfer resistance is 39Ω, indicating that the cathode material has a lower impedance during the electrochemical reaction, further enhancing its electrochemical performance. Not only that, the cathode material also performs well in mechanical properties. Its tensile strength reaches 116MPa, indicating that the cathode material can still meet higher mechanical strength requirements while having excellent electrochemical properties. This feature makes the cathode material more reliable and durable in practical applications. Considering the electrochemical properties and mechanical properties, the cathode material of Example 5 obviously has significant comprehensive advantages.
[0149] In Example 1 and Examples 4-7, the main difference is that the mass ratio of the treated material to the 6mol / L KOH solution is different, that is, the immersion concentration ratio of the alkali solution to the material varies from 1:1 to 1:10. This different mass ratio has a significant effect on the final porous structure and electrochemical properties of the material. As the KOH solution treatment ratio increases, the pore size of the material changes within a certain range. Different KOH treatment ratios affect the erosion depth of the material and the degree of corrosion on the carbon fiber surface. Experiments show that Example 5 (KOH concentration of 1:5) produces the optimal pore size distribution, so that the material has pores suitable for zinc ion transmission. KOH solution is a strong alkaline corrosive agent, and different ratios will produce different degrees of corrosion on the surface and internal structure of the material. An appropriate KOH ratio (such as 1:5) can form a uniform microporous or mesoporous structure on the surface and inside of the material, while too high or too low concentrations may lead to uneven pore structure and affect the effective transmission path of zinc ions. Under the condition of 1:5, the pore size distribution and structural optimization inside the material can provide an efficient channel for zinc ions, reduce the ion transport resistance, and thus enhance the electrochemical properties of the material.
[0150] Example 5 shows a higher specific surface area, while the specific surface area is reduced compared to Example 7 with a higher treatment ratio (such as 1:10). The increase in specific surface area helps the material provide more active sites, thereby improving the activity of the electrode reaction. When the KOH concentration is at the optimal ratio of 1:5, the formation of the pore structure and the specific surface area reach the best balance. Too high a concentration (such as 1:10) will lead to excessive corrosion, which may cause surface irregularities and collapse of pores, thereby reducing the specific surface area. Lower concentrations are not enough to form sufficient pore structures, so the optimal ratio of KOH treatment gives the material surface more active sites and increases the specific surface area.
[0151] The specific capacity reaches the highest in Example 5, which shows that the optimal pore size distribution and large specific surface area promote the electrochemical reaction, especially the embedding and extraction process of zinc ions. The moderate pore size and uniform porous structure can provide a better channel for the reversible embedding and extraction of zinc ions. The optimization of the pore structure ensures the transmission efficiency of zinc ions, reduces the polarization effect, and thus improves the specific capacity. When the mass ratio is 1:5, the material has a relatively uniform pore size distribution and a good pore structure, which can accommodate more zinc ions during the charge and discharge process, thereby improving the specific capacity.
[0152] The KOH solution treatment ratio of Example 5 performs best in preparing coaxial gradient porous nano core-shell structure cathode materials. The optimal KOH concentration can form a uniform and moderate pore distribution inside the material, maximize the specific surface area, and provide an efficient zinc ion transmission path. The appropriate amount of KOH treatment can increase the porosity without destroying the material structure, improve the specific capacity and energy density, and ensure that the material maintains a high stability during long cycles. Low charge transfer resistance ensures the high efficiency of the electrochemical reaction and gives the material good conductivity.
[0153] In the comparison between Example 5 and Example 8, the only variable is the change in doping material, that is, the change from carbon quantum dots (CDs) to carbon nanotubes (CNTs). According to the data, the performance of CDs is better than that of CNTs overall. Example 5 (CDs doping) has a more uniform pore size distribution and a higher specific surface area, while Example 8 (CNTs doping) is slightly inferior to the former. Due to its small size and unique nano-size effect, CDs can be more evenly distributed in the carbon fiber structure after doping, bringing a higher specific surface area to the carbon fiber membrane. The size of CDs is usually between a few nanometers and tens of nanometers, and more micropores or mesopores can be formed compared to CNTs (usually with a diameter of tens of nanometers to hundreds of nanometers). These pores provide more paths for zinc ion transport and electrolyte penetration, thereby improving the specific surface area and pore size uniformity of the material. In contrast, CNTs are larger in size and have a one-dimensional tubular structure. The distribution uniformity and pore size regulation ability in the material are slightly inferior, resulting in a slightly lower specific surface area and pore size distribution than CDs doped materials.
[0154] The specific capacity and energy density of Example 5 are better than those of Example 8. The specific capacity and energy density are greatly affected by the active sites and electrode structure of the material. CDs present a zero-dimensional structure in the material, which can not only form more active sites, but also can be fully filled in the gaps between carbon fibers due to its smaller size, thereby forming a uniform distribution of active sites on the surface and inside of the material. Although the tubular structure of CNTs helps to improve conductivity, its one-dimensional tubular morphology limits the embedding position and path of zinc ions, making the specific capacity and energy density slightly lower. The porous structure and increase in active sites after CDs doping provide more sufficient space for the embedding and extraction of zinc ions, making its specific capacity and energy density better.
[0155] The zero-dimensional structure of CDs not only increases the porosity and specific surface area of the material, but also provides more active sites, effectively improving the specific capacity and energy density. Compared with CNTs, CDs can be more evenly dispersed in the material, thereby optimizing the pore size distribution, reducing the charge transfer resistance, and improving the cycle stability. Although CNTs have good conductivity, in this type of core-shell structure material, CDs show stronger pore regulation ability, active site provision ability and structural stability. Therefore, the overall performance of CDs-doped materials is better than that of CNTs-doped materials.
[0156] In Example 9, the inner and outer layer materials were swapped: the outer layer was changed to SAN-doped PAN, and the inner layer was CDs-doped PAN. The outer layer of SAN-doped PAN has higher molecular rigidity and tensile strength, while CDs-doped PAN is generally relatively more flexible. Moving SAN-doped PAN to the outer layer makes the material more resistant to external tensile forces as a whole, so the tensile strength is slightly increased. The electrochemical performance of Example 9 decreased, and the reasons may be: CDs has a more significant effect on improving conductivity and active sites. When CDs-doped PAN is used as the outer layer material, it has more direct contact with the electrolyte, provides more reaction sites, and helps the transmission and storage of zinc ions; CDs has good conductivity, and placing it in the outer layer can effectively reduce the charge transfer resistance. However, in Example 9, CDs-doped PAN becomes the inner layer, the contact with the electrolyte is reduced, the utilization rate of active sites is reduced, and the specific capacity and energy density are reduced; SAN-doped PAN is in the outer layer, the outer layer has poor conductivity, and the charge transfer resistance at the interface is increased, resulting in an increase in charge transfer resistance. Since it is difficult for SAN-doped PAN materials to form an ideal gradient pore structure after KOH treatment, the pore distribution of the outer layer is not as effective as that of the CDs-doped PAN in the original design. The lack of this gradient pore structure leads to the narrowing of the zinc ion channel, affecting the ion transmission efficiency. At the same time, the role of the pore structure in the inner CDs-doped PAN is weakened, affecting the penetration of the electrolyte and ion diffusion, further reducing the specific capacity and cycle performance of the material.
[0157] Compared with Example 5, Comparative Example 2 lacks the KOH treatment step, and the performance is greatly reduced compared with other embodiments. The specific surface area and pore size distribution of Comparative Example 2 are significantly lower than those of other embodiments. KOH treatment can significantly increase the controllability of specific surface area and pore structure, which is crucial for the ion channels of zinc ion batteries. KOH treatment will cause chemical etching on the surface of the material, causing the carbon fiber membrane material to form abundant micropores and mesopores. This etching effect can increase the porosity of the material, generate more effective ion channels in the material, and increase the specific surface area of the material. Optimization of the pore structure can improve the diffusion rate and transmission efficiency of zinc ions. Comparative Example 2, which lacks KOH treatment, fails to generate these pore structures, resulting in a significant reduction in specific surface area and insufficient zinc ion channels, thereby limiting the ion transmission capacity of the material.
[0158] The specific capacity and energy density of Comparative Example 2 are lower than those of other embodiments. KOH treatment will form abundant active sites on the surface of the material. These sites play a key role in the electrochemical reaction and can improve the specific capacity and energy density of the material. The more active sites there are, the greater the amount of ions that the material can carry during the charge and discharge process, thereby improving the specific capacity and energy density. Comparative Example 2, which lacks KOH treatment, lacks these active sites, resulting in a significant reduction in its energy storage capacity. In addition, the pore structure after KOH treatment can also provide a higher electrolyte contact area, improve the efficiency of the electrochemical reaction, and thus further improve the energy density.
[0159] The charge transfer resistance of Comparative Example 2 is significantly higher than that of other embodiments, indicating that its conductivity is poor. KOH treatment creates more pores and active sites in the carbon fiber membrane material, reduces the charge migration resistance, and thus optimizes the electrode conductivity. The microporous structure after KOH etching can effectively shorten the migration path of ions and electrons, reduce internal resistance, and improve electrode reaction efficiency. However, due to the lack of KOH treatment steps in Comparative Example 2, the charge transfer path is limited, resulting in an increase in electron migration resistance and a significant increase in charge transfer resistance, which will directly affect the electrochemical properties of the material and make its reaction efficiency worse during the charge and discharge process.
[0160] Through the above analysis, the effect of KOH treatment on the pore structure, active site distribution, cycle stability and charge transfer resistance of the material is extremely significant. Due to the lack of this step, Comparative Example 2 leads to a decrease in porosity and specific surface area, insufficient active sites, which affects the efficiency of zinc ion diffusion and electron migration, resulting in a significant decrease in specific capacity, energy density and cycle life. In addition, the higher charge transfer resistance further limits its electrochemical reaction rate. In summary, KOH treatment is a key step in improving the performance of this type of coaxial gradient porous nano core-shell structure cathode material.
[0161] Compared with Example 5, the specific surface areas of Comparative Examples 1 and 2 are significantly lower, being 700 m2 / g and 760m 2 / g, while the specific surface area of Example 5 is 880m 2 / g. This difference is mainly attributed to the optimized design of the gradient porous structure in Example 5, which makes the material surface have more active sites and significantly improves the adsorption capacity of zinc ions. In the comparative example, the pore structure is relatively simple or rough, and it is unable to effectively provide more zinc ion adsorption sites, resulting in a small specific surface area, and the electrochemical performance is therefore limited.
[0162] Compared with Example 5, the pore size distribution of Comparative Examples 1 and 2 is significantly wider, 1-10 nm respectively, while the pore size distribution of Example 5 is narrower, only 1.1-3.8 nm. This difference is mainly due to the special air-jet spinning process used in Example 5 and the introduction of carbon nanodots, which makes the pore size control more precise, thereby optimizing the storage environment of Zn2+. In the comparative example, the wider pore size distribution reflects the inhomogeneity of the internal structure of the material, resulting in a decrease in the stability of the electrode performance and may affect the storage and release efficiency of zinc ions.
[0163] Compared with Example 5, the specific capacities of Comparative Examples 1 and 2 are significantly lower, 200 mAh / g and 210 mAh / g, respectively, while the specific capacity of Example 5 reaches 300 mAh / g. This difference is attributed to the optimized pore structure and higher specific surface area in Example 5, which greatly improves the storage capacity of Zn2+. In contrast, the materials in the comparative examples have limited zinc ion storage capacity due to insufficient specific surface area and unsatisfactory pore structure, thereby reducing the overall electrochemical performance.
[0164] The energy densities of Examples 1, 2, 3, 5, 6, and 8 are 180Wh / kg, 185Wh / kg, 183Wh / kg, 190Wh / kg, 180Wh / kg, and 180Wh / kg, respectively, showing the significant advantages of the material in energy storage. This is due to the optimized pore structure, which effectively improves the zinc ion storage capacity of the material, thereby improving the overall energy density. In contrast, the energy density of Comparative Examples 1 and 2 is relatively low, mainly because their pore structures are poor, which limits the effective storage of zinc ions, thereby affecting the energy density performance of the material.
[0165] The cycle stability of Examples 1, 2, 3, 5, 6, and 8 is very high (94%-98%), showing the excellent performance of the material under long cycle life, which is due to the porous core-shell structure effectively buffering the volume change of the electrode material during the charge and discharge process, ensuring stable electrochemical performance. In contrast, the cycle stability of Comparative Examples 1 and 2 is poor (85% and 87%), which may be due to the unstable material structure, resulting in significant performance degradation after multiple charge and discharge cycles.
[0166] Compared with Example 5, the charge transfer resistance of Comparative Examples 1 and 2 is significantly higher, 65Ω and 70Ω respectively, while the charge transfer resistance of Example 5 is only 39Ω. This shows that the electrode material in Example 5 has a superior conductivity, which is mainly attributed to its optimized pore structure and uniformly distributed conductive paths, which effectively promotes the rapid transfer of charge in the electrode material. Relatively speaking, in Comparative Examples 1 and 2, the material has fewer conductive paths or the pore structure is not conducive to the transfer of charge, resulting in a higher charge transfer resistance, which in turn limits the power output and overall electrochemical performance of the battery.
[0167] Comparative Example 3 lacks HF acid treatment. HF acid treatment is used to remove certain inorganic components in the fiber membrane or generate a specific porous structure. This treatment can usually form micropores and mesopores suitable for zinc ion transmission on nanofibers. The lack of HF acid treatment will cause more inorganic impurities to remain in the fiber membrane, resulting in the material's pore structure being not uniform enough and the overall specific surface area being reduced. This will directly affect the material's ion transmission efficiency and the permeability of the electrolyte. Due to the insufficient pore structure and the lack of support for micropores and mesopores, the diffusion path of the electrolyte in the material increases, hindering the efficient transmission of zinc ions, resulting in a decrease in specific capacity and energy density. The uneven pore structure may cause the local current density to increase in long-term circulation, thereby aggravating the attenuation of the material and reducing the cycle stability. After the HF acid treatment is missing, the microporous structure of the material is reduced, the contact area between the electrolyte and the electrode active sites is reduced, and the charge transfer resistance is increased.
[0168] Comparative Example 4 uses weak alkali treatment instead of concentrated alkali KOH treatment. The strong alkalinity and strong corrosiveness of KOH will etch the surface of the carbon material at high temperature, generate abundant micropores and mesoporous structures, and optimize the pore distribution and pore size of the electrode material. However, the etching ability of weak alkali (such as NaHCO3 or Na2CO3) treatment is limited, resulting in insufficient micropore generation on the surface of the material, and the zinc ion channel path cannot be effectively optimized. This will cause the electrolyte to diffuse slowly and affect the electrode reaction efficiency. Due to the small number of pore structures, the number of active sites inside the material is reduced, and the incompleteness of the electrode reaction leads to lower specific capacity and energy density. The undesirable pore structure will increase the penetration resistance of the electrolyte during the cycle, and cause the charge transfer efficiency to decrease, the charge transfer resistance to increase, and at the same time, under long-term circulation, the utilization rate of the active sites and the stability of the material structure are poor, showing lower cycle stability.
[0169] Comparative Example 5 uses vanadium-based oxide (V2O5) to dope PAN. V2O5 has good redox activity, but its conductivity is relatively low. The use of V2O5-doped PAN fiber material may cause the overall conductivity of the material to decrease, thereby affecting the charge transfer efficiency in the electrochemical reaction. The active sites of the vanadium-based oxide do not completely match the electrochemical active sites of the electrode material, which may form unfavorable interactions during the embedding and extraction of zinc ions, resulting in a decrease in specific capacity and energy density. The vanadium-based oxide-doped PAN material after electrospinning may not form an ideal gradient pore or microporous structure in structure, so that the electrolyte and zinc ions cannot be effectively distributed in the fiber membrane, thereby reducing the efficiency of ion transfer. After V2O5 doping, the structure of the material may be prone to deformation and decreased stability during long-term circulation. The electrochemical stability of vanadium-based oxides is not as stable as that of carbon-based materials, resulting in decreased cycle performance.
[0170] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a coaxial gradient porous nano core-shell structure cathode material, characterized in that: The following steps are involved: (1) dissolving a conductive carbon nanomaterial and a high molecular polymer in a solvent to obtain a precursor solution A; A styrene-acrylonitrile copolymer and a high molecular polymer are dissolved in a solvent to obtain a precursor solution B; the precursor solution A is injected into the outer channel of a coaxial air nozzle, and the precursor solution B is injected into the inner channel of the coaxial air nozzle, or the precursor solution A is injected into the inner channel of the coaxial air nozzle, and the precursor solution B is injected into the outer channel of the coaxial air nozzle, and coaxial air-jet spinning is performed to obtain an air-jet spinning membrane with a nano core-shell structure; the conductive carbon nanomaterial is selected from one or more of carbon quantum dots, graphene quantum dots, carbon nanotubes, fullerenes and graphene oxides; the high molecular polymer is selected from one or more of polyacrylonitrile, polyamic acid, polybenzimidazole, polypyrrole and polyetherimide; (2) immersing the air-jet spun membrane with a nano core-shell structure obtained in step (1) into a 3-aminophenol solution, then adding methyltriethoxysilane and ammonia water, and then injecting a formaldehyde solution to obtain a surface-modified air-jet spun membrane with a nano core-shell structure; (3) subjecting the surface-modified air-jet spinning membrane with a nano core-shell structure obtained in step (2) to a pyrolysis carbonization treatment in an inert atmosphere to obtain a nano hybrid carbon fiber membrane material with a porous structure; (4) using an acid solution to treat the nano hybrid carbon fiber membrane material with a porous structure obtained in step (3), mixing the treated material with a strong alkaline solution, and performing a carbonization treatment in an inert atmosphere to obtain the coaxial gradient porous nano core-shell structure cathode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the conductive carbon nanomaterial to the high molecular polymer is (0.5-1):(10-15); the mass ratio of the styrene-acrylonitrile copolymer to the high molecular polymer is (5-10):(10-15).
3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the conductive carbon nanomaterial in the precursor solution A is 10-15 wt %; the concentration of the styrene-acrylonitrile copolymer in the precursor solution B is 5-20 wt %.
4. The preparation method according to claim 1, characterized in that: In step (1), the process parameters of the coaxial air-jet spinning are: the jet rate of the inner channel is 0.5-2.0 mL / h; the jet rate of the outer channel is 1.0-5.0 mL / h.
5. The preparation method according to claim 1, characterized in that: In step (2), the volume ratio of the 3-aminophenol solution, methyltriethoxysilane, ammonia water and formaldehyde solution is 5:(0.5-1.5):(0.5-1.5):(0.5-1.5).
6. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the pyrolysis carbonization treatment is 750-800°C.
7. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the treated material to the strong alkaline solution is 1:(3-7).
8. The preparation method according to claim 1, characterized in that: In step (4), the specific operation of the carbonization treatment is: heating to 700-800°C at a heating rate of 1-3°C / min and maintaining for 0.5-2h.
9. A coaxial gradient porous nano core-shell structure cathode material prepared by the method according to any one of claims 1 to 8.
10. Use of the coaxial gradient porous nano core-shell structure cathode material according to claim 9 in the preparation of zinc ion batteries.
Citation Information
Patent Citations
Preparation method of high-power aqueous zinc ion battery positive electrode material
CN110828802A
Preparation method of manganous oxide composite material for aqueous zinc ion battery
CN114335471A
N-doped metal cobalt carbon nanofiber composite material and preparation method and application thereof
CN108847492A
Nano silicon-carbon composite electrode material and lithium battery thereof
CN115295785A
Nanofiber composite and preparation method thereof
WO2013115497A1